Online options for future conferences will have an important positive impact for Early Career Researchers in pediatric pain - Caroline Hartley (Wiley, 2021)
Abstract The extent to which the COVID‐19 pandemic will have a negative impact on Early Career Researchers (ECRs) within the field of pediatric pain and in general is still unclear, but it is likely to be far reaching and may disproportionality affect women. Yet, there is also great opportunity to take advantage of the rapid adaptions to working life that we have all undertaken during the pandemic. In particular, continuing to have online options for conference attendance I think will have a positive impact on ECRs, and in particular female ECRs, now and in the future. Moreover, the pediatric pain research community is relatively small and highly international; by enabling wider participation in our conferences we will diversify our research output and expedite our aim of providing better treatment of pediatric pain.